The cardiovascular effects of interleukin-6 inhibition in patients with severe coronavirus-19 infection - Michael S Binder; Clinton Timmerman; Biwar Marof; Yingxing Wu; Adegbenga Bankole; Ido Heletz (Journal of International Medical Research)
Objective The coronavirus disease 2019 (COVID-19) pandemic illustrated the relationship between cardiac arrhythmias and pro-inflammatory states. Pro-inflammatory cytokines, including interleukin-6 (IL-6), have significant effects on cardiac conduction. Atrial or ventricular arrhythmias occurring while infected results in a doubling of mortality. Tocilizumab, a monoclonal antibody that blocks the IL-6 receptor, is associated with improved mortality and is believed to be related to immune modulation of the COVID-19–related hyperinflammatory state. Methods A single-center retrospective review of all patients with severe COVID-19, defined as admission to an intensive care unit or requirement of respiratory or circulatory support, from March 2020 through March 2022, was conducted. Patients who received or did not receive tocilizumab were grouped into the treatment and control groups, respectively. Results Four hundred seventy-three patients were reviewed and 400 met the criteria for inclusion in our study. There were 305 patients (age, 63 ± 13 years, 58% male) in the control group and 95 (age, 57 ± 15 years, 51% male) in the treatment group. In-hospital mortality was greatly reduced with tocilizumab compared with controls (44.2% vs 85.9%, p < 0.001) and new-onset atrial fibrillation (AF) showed a statistically significant reduction (17.8% vs 29.5%, p = 0.019). New-onset wall motion abnormalities, potentially related to myocarditis or acute coronary syndrome, also trended toward significance with tocilizumab (7.7% vs 15.7%, p = 0.10). Deep vein thrombosis, pulmonary embolism, stroke, and sustained ventricular arrhythmias did not meet statistical significance. Conclusion As expected, tocilizumab did show significant improvement in mortality. Tocilizumab also showed a significant reduction of new-onset AF. Other cardiac structural endpoints did not reach statistical significance. Abstract Presentations A preliminary version of this research was presented during a regional conference at the Mid-Atlantic Capital Cardiology Symposium (MACCS) on 19 November 2023.